Управління депозитним портфелем комерційного банку - Швирид, Дмитро Володимирович; Shvyryd, Dmytro (ЦНТУ, 2024)
У роботі розглянуто сутність, функції депозитного портфеля та сформовано принципи його формування; здійснено аналіз динаміки та структури депозитного портфелю банківських установ України; проведено аналіз фінансової діяльності та депозитного портфелю АТ КБ «ПриватБанк»; запропоновано напрями підвищення ефективності управління депозитним портфелем. Приділена увага системи управління депозитного портфелю АТ КБ «ПриватБанк», напрямам підвищення ефективності управління депозитним портфелем, оцінці депозитним портфелем в банківскій системі Досліджено ефективність формування депозитного портфеля на прикладі АТ КБ "ПриватБанк". Запропоновано: комплекс методів оцінки управління депозитним портфелем в АТ КБ «ПриватБанк», систему забезпечення якості депозитного портфеля АТ КБ «ПриватБанк» яка складається з трьох блоків, які вирішують питання загроз, ризиків та безпеки, систематизовано чинники які впливають на управління депозитним портфелем банку; з метою зменшення концентрації ризиків у депозитному портфелі та окремих депозитів розроблена таблиця «профілю ризиків». The work examines the essence and functions of the deposit portfolio and outlines the principles of its formation; an analysis of the dynamics and structure of the deposit portfolio of banking institutions of Ukraine was carried out; an analysis of the financial activity and deposit portfolio of JSC CB "PrivatBank" was carried out; directions for improving the efficiency of deposit portfolio management are proposed. Attention is paid to the deposit portfolio management system of JSC KB "PrivatBank", directions for improving the efficiency of deposit portfolio management, assessment of the deposit portfolio in the banking system. The effectiveness of the formation of the deposit portfolio was studied on the example of JSC CB "PrivatBank". It is proposed: a complex of deposit portfolio management assessment methods in JSC KB PrivatBank, a system for ensuring the quality of the deposit portfolio of JSC KB PrivatBank, which consists of three blocks that solve the issues of threats, risks and security, systematized factors that affect the management of the bank's deposit portfolio; in order to reduce the concentration of risks in the deposit portfolio and individual deposits, a "risk profile" table was developed.
Commercial bank deposit portfolio management
Keywords: депозити; депозитний портфель; фінансовий стан; шляхи оптимізації; вплив чинників; динаміка та структура; методи управління; аналітична оцінка; напрями підвищення ефективності; deposits; deposit portfolio; financial condition; ways of optimization; influence of factors; dynamics and structure; management methods; analytical evaluation; directions for improving efficiency